Cultural Ecosystem of Creative Place: Creative Class, Creative Networks and Participation in Culture - Anders-Morawska, Justyna (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
The scope of this paper is to conceptualise a data-based research framework for the role of creative networks in cultural exchange. Participation in culture measured as audience per 1000 residents and expenditures on culture-related activities were analysed in relation to such territorial assets as accessibility to creative infrastructure, the economic status of residents, the governance networks of civil society, and cultural capital. The results indicate how accessibility, governance networks, and cultural capital contribute to participation measured via audience indicators while a low poverty rate has explanatory value with respect to expenditures on culture.